Motivational Influences on Volunteer Activities and Field Satisfaction: Insights from Medical Students in Peshawar - Khan, Kamran; Shah, Khoula; Akhtar, Laiba; Zakir, Mahnoor; Ahmad, Iftikhar; Jahan, Sarwat (Journal of Rawalpindi Medical College, 2025)
Objective: This study aimed to assess the level of satisfaction with the medical field among medical students in Peshawar. Methods: A cross-sectional analytical study was conducted on 329 medical students from 1st May 2024 to 15th July 2024, in the Northwest School of Medicine, across seven private medical colleges in Peshawar. Data was collected through a structured questionnaire covering demographics, volunteer experience, motivations, and satisfaction levels. Statistical analysis, including Pearson Chi-Square tests, was performed using SPSS version 26 to examine associations between volunteer status and field satisfaction and stress levels. Results: Out of all the participants, 183 (55.6%) had volunteer experience, showing significantly higher field satisfaction p < 0.001) than non-volunteers. Additionally, volunteers reported lower stress levels (p = 0.028), with motivations including helping others, skill development, and social connections. Time constraints were a significant barrier for non-volunteers, while the lack of institutional support also limited volunteer involvement. Conclusion: Volunteer activities have a positive influence on field satisfaction and reduce stress levels in medical students, suggesting that their integration into medical education may enhance students’ overall well-being. Addressing logistical barriers and expanding volunteer support in academic institutions could further benefit students and the communities they serve. Keywords: Motivation, Social Support, Adaptation, Psychological Community-Institutional Relations.